1910
DOI: 10.1037/h0074736
|View full text |Cite
|
Sign up to set email alerts
|

Reaction to rhythmic stimuli with attempt to synchronize.

Abstract: In my paper on • The Complication Experiment and Related Phenomena' 2 I stated my conclusion that the typical illusion of the so-called ' complication experiment' depends on a rhythmic reaction which the subject makes mechanically : that the result of this reaction (the tolerably clear vision of the pointer) seems to the subject to be synchronous with the sound or whatever discrete stimulus is used, but is really achieved previous to the said stimulus (giving negative error), or subsequent thereto (giving posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(78 citation statements)
references
References 0 publications
4
73
0
1
Order By: Relevance
“…Correlational coefficients for best fits of the latter model are indicated above the bars 1 autocorrelation). Second, consistent with previous findings , we found evidence of higher order error correction (negative Lag 3 autocorrelation) only when auditory information was present, and in a new finding, particularly when it was less salient (complex rhythm, small magnitude condition).The current study contributes to a growing literature demonstrating that the auditory advantage in sensorimotor synchronization, first observed in comparisons between (auditory) metronome ticks and (visual) flashing lights (e.g., Bartlett & Bartlett, 1959;Chen et al, 2002;Dunlap, 1910;Jäncke et al, 2000;Patel et al, 2005;Repp & Penel, 2002, 2004, may be more nuanced than previously thought. For example, recent studies have shown that visual performance for simple rhythms improves to auditory levels when visual information is continuous rather than discrete (Gan et al, 2015;Iversen et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…Correlational coefficients for best fits of the latter model are indicated above the bars 1 autocorrelation). Second, consistent with previous findings , we found evidence of higher order error correction (negative Lag 3 autocorrelation) only when auditory information was present, and in a new finding, particularly when it was less salient (complex rhythm, small magnitude condition).The current study contributes to a growing literature demonstrating that the auditory advantage in sensorimotor synchronization, first observed in comparisons between (auditory) metronome ticks and (visual) flashing lights (e.g., Bartlett & Bartlett, 1959;Chen et al, 2002;Dunlap, 1910;Jäncke et al, 2000;Patel et al, 2005;Repp & Penel, 2002, 2004, may be more nuanced than previously thought. For example, recent studies have shown that visual performance for simple rhythms improves to auditory levels when visual information is continuous rather than discrete (Gan et al, 2015;Iversen et al, 2015).…”
Section: Discussionsupporting
confidence: 79%
“…The few studies that have examined visual or tactile pacing signals reveal contradictory results. Kolers and Brewster (1985) report a reduction in asynchrony under conditions applying visual signals rather than clicks (and even positive asynchronies under conditions with very short intertap intervals), thus replicating earlier studies (Dunlap, 1910;Fraisse, 1948;Miyake, 1902).…”
Section: Manipulating Features Of the Pacing Signalsupporting
confidence: 70%
“…This means that the tap precedes the click by about 20 to 80 ms. This effect was described already more than 100 years ago (e.g., Dunlap, 1910;Johnson, 1898;Miyake, 1902) and has been replicated in a number of studies (e.g., Aschersleben & Prinz, 1995, 1997Fraisse, 1980;Kolers & Brewster, 1985;Mates, Müller, Radil, & Pöppel, 1994;Repp, 2000;Thaut, Tian, Azimi-Sadjadi, 1998;Vos, Mates, & van Kruysbergen, 1995, Wohlschläger & Koch, 2000.…”
Section: Fig 1 the Synchronization Taskmentioning
confidence: 95%
“…It has long been known that human beings have a "sense of rhythm" and orchestrate by reference to cues in the preceding, rather than contemporaneous cycle (Dunlap, 1910), but it has not been recognized generally that both the maintenance of a natural spontaneous rhythm and entrainment to foreign rhythms might be referable to very simple oscillatory cells or networks. On the other hand, in spite of the existence of resettable neurons in many molluscs and crustacea (and presumably in all higher animals), and their known ability to interact by means of both excitatory and inhibitory synaptic connections in coordinating a wide variety of rhythmic activities, it remains a mystery that no mammal besides man can perform any sort of whole-body group rhythmic activity that is truly synchronized.…”
Section: Discussionmentioning
confidence: 99%